Metropolitan Regions: Challenges for Sustainability and Governance of Periurban Areas in Brazil. - Prof. Dr. Martin Coy; Dr. Simone Sandholz; Dr. Tobias Töpfer; Dr. Frank Zirkl (Confins)
Metropolization has become a global phenomenon of urbanization. In a highly urbanized country like Brazil this process is visible in mega cities as well as in regional metropoles, leading to vast urbanized areas stretching from the core cities to formerly distant neighborhood municipalities. Enormous urban agglomerations like the Macrometropole Paulista are the impressive result, however coming with significant challenges in governing such huge but highly fragmented areas. Especially the most populous Brazilian metropolitan areas have to deal with peri-urban development challenges like the lack of infrastructure and public security or new forms of fragmentation that come along with social and ecological problems. Overcoming these challenges is a remarkable task for the municipal, regional and national level. Based on a classification of different phases of peri-urban development that can be distinguished since the 1960s this paper analyses the development of Brazil’s metropolitan areas. Different forms of governance as well as concepts of sustainable approaches to deal with urban challenges are assessed based on the cases of Sao Paulo, Curitiba and Recife.